2020
DOI: 10.2147/opth.s237457
|View full text |Cite
|
Sign up to set email alerts
|

<p>Optimum Refractive Target in Patients with Bilateral Implantation of Extended Depth of Focus Intraocular Lenses</p>

Abstract: Purpose: To determine the refractive target of extended depth of focus (EDOF) intraocular lenses in dominant and non-dominant eyes which provides the best binocular vision at all ranges after cataract surgery. Patients and Methods: This retrospective, single-center, non-comparative study included 47 patients who had undergone bilateral cataract surgery with implantation of EDOF IOLs (Tecnis Symfony or Tecnis Symfony Toric) targeting emmetropia in both eyes. Binocular uncorrected visual acuity at distance (UDVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
(36 reference statements)
1
4
0
1
Order By: Relevance
“…In addition, subjective optimal correction and postoperative patient satisfaction were high. The studies published over the last two years are in line with the current findings, highlighting good visual outcomes after Tecnis Symfony implantation [8][9][10][11][12]. However, most authors agree that near vision might be limited in some patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, subjective optimal correction and postoperative patient satisfaction were high. The studies published over the last two years are in line with the current findings, highlighting good visual outcomes after Tecnis Symfony implantation [8][9][10][11][12]. However, most authors agree that near vision might be limited in some patients.…”
Section: Discussionsupporting
confidence: 88%
“…Even with distance corrected refraction, it has been observed that some patients achieve good visual acuities (≤ 0.1 LogMAR or 0.8 decimal) as near as 20 cm, whereas others only reach a sharp vision until one meter. Some authors have suggested that targeting a mild myopia in non-dominant eye improves postoperative outcomes [ 10 ]. The variability in the range of clear vision with multifocal IOL has been attributed to several factors, but the influence on extended focus IOLs has not been extensively explored.…”
Section: Discussionmentioning
confidence: 99%
“…We applied mini-monovision in all patients, with a target of −0.50 D in the non-dominant eye and achieved a postoperative MRSE of −0.46±0.35 D. Figure 1 shows that the postoperative MRSE of the dominant and mini-monovision eyes was close to their respective target refractions (0 and −0.50 D). A target refraction between −0.21 D and −0.63 D was reported by Jackson et al 21 as the optimal range for nondominant eyes implanted with the Tecnis Symfony IOL (Johnson and Johnson) during bilateral cataract surgery. Using the same EDOF IOL with mini-monovision (target −0.50 D).…”
Section: Discussionmentioning
confidence: 90%
“…In order to achieve a better near functional vision, a slightly myopic correction (mini-monovision) in the non-dominant eye has been recommended by the experts. 8 , 14 , 28 Although most patients in our study had a good distance and intermediate functional visual acuity using this approach, only 18% have respectively achieved complete spectacle independence. This percentage might seem very low, but it has to be considered, that we decidedly encouraged our patients to use reading glasses for long-term reading to avoid fatigue, even when they had a good functional reading vison in one eye.…”
Section: Discussionmentioning
confidence: 62%